Examining Big Data in Medicine: Applications, Challenges and Benefits - Matthew N. O. Sadiku; Kazeem B. Olanrewaju; Sarhan M. Musa (European Scientific Journal, ESJ, 2020)
Advances in technology have created and will continue to create changes in medical science and practice. In recent years, the medical community has seen massive amount of information, which is collectively known as “big data.” Literatures from various sources were reviewed to explore the application of data analytics in medicine, the benefits and challenges associated with its use.With recent advances in digital technology, the ability to gather and examine big data has become far cheaper and faster. With the promise of data-driven knowledge and intelligent decision-making, big-data projects are going on in every branch of medicine. However, the process of engaging stakeholders to benefits fromthe information provided by big data remain a major issue. This paper presents how big data and big data analytics are used in medicine.